Morbidity and mortality in preterm infants less than 29 weeks of gestational age - Marques, B.R. (2019)
Background: Preterm birth is certainly a public health problem. Aside from being an important cause of mortality, prematurity increases the risk of serious lifetime disabilities. Objective: To assess the overall survival, causes of death and neonatal morbidities associated with prematurity of newborns less than 29 weeks of gestational age (GA). Methods: Retrospective study including all preterm infants less than 29 weeks of GA admitted to the level III Neonatal Intensive Care Unit (NICU) at Centro Hospital São João in Porto, Portugal, between January 1st, 2005 and December 31st, 2016. Newborns were grouped into three groups according to their GA: G23+0-24+6, G25+0-26+6, G27+0-28+6. Results: In this 12-year-period, 160 preterm neonates less than 29 weeks of GA admitted to this NICU met our inclusion criteria. Overall deaths were 60 (37.5%), variating between 25 (92.6%) in the G23+0-24+6, 23 (46%) in the G25+0-26+6 and 12 (14.5%) in the G27+0-28+6. The leading causes of death were intraventricular hemorrhage (IVH) and sepsis. Early neonatal mortality was 20.6%. Among survivors, 41% had bronchopulmonary dysplasia (BPD), 69% developed late sepsis, 56% retinopathy of prematurity (ROP), 44% IVH and 10% cystic periventricular leukomalacia (cPVL). Conclusions: Mortality rates in this preterm group were high in spite of all the technological and scientific advances. Pulmonary conditions (respiratory distress syndrome and BPD), sepsis and neurologic outcomes (ROP, IVH and cPVL) were still major causes of morbidity. In line with other series, the limit of viability in this cohort of preterm infants is 25 weeks of GA. Prenatal, perinatal and postnatal care still all have a long road ahead, especially when it comes to these “gray zone” newborns.